Impact of modern slavery on the psychosocial wellbeing of children in Bodija market, Ibadan, Oyo State. (2024)
In Nigeria, modern slavery manifests in various ways, such as child labor, human trafficking, forced begging, and domestic servitude. These problems are driven by a range of socio economic issues. Children who are caught in these practices suffer physical and emotional harm, affecting their mental health. This study looked into the effect of modem slavery on the mental and social health of children in the Bodija market in -Ibadan, Oyo State. A descriptive survey method was used. The study's sample consisted of children engaged in child labor at the Bodija market. Respondents were chosen using a purposive sampling method, focusing on the market area. Data was collected using a custom questionnaire. The study tested four hypotheses using Pearson Product Moment Correlation (PPMC) with a significance level set at 0.05. The results showed a significant link between modem slavery and the psychological health of children in Bodija market, Ibadan, Oyo State (r (152) - .504**, p<.05), leading to the rejection of the null hypothesis. The second finding indicated a significant correlation between modem slavery and the cognitive health of these children (r (152) = .755**, p<.05). The third hypothesis found a significant relationship between modem slavery and children's behavioral health in Bodija market (r (152) = .670**, p<.05). The final result revealed a significant link between modem slavery and the social health of children in Bodija market (r (152) - . 163 , p<.05). These findings suggest that modem slavery has a substantial impact on the psychological, cognitive, behavioral, and social health of children in the market. The study concluded that efforts to reduce children's vulnerability require increased access to education and better enforcement of child protection laws. Without proper education, children are at greater risk of hazardous work or being exploited by traffickers offering false promises. The study recommended that social workers develop educational programs to raise awareness among parents and policymakers about the negative effects of child exploitation, particularly on children's mental and social well-being